2023
DOI: 10.3390/molecules28020890
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Conformationally Restricted Carbonic Anhydrase Inhibitors

Abstract: This paper reports an investigation into the impact of pyridyl functional groups in conjunction with hydroxide-substituted benzenesulfonamides on the inhibition of human carbonic anhydrase (CA; EC 4.2.1.1) enzymes. These compounds were tested in vitro of CA II and CA IX, two physiologically important CA isoforms. The most potent inhibitory molecules against CA IX, 3g, 3h, and 3k, were studied to understand their binding modes via X-ray crystallography in adduct with CA II and CA IX-mimic. This research further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Data on crystals of the complexes were collected using synchrotron radiation at the XRD2 beamline at Elettra Synchrotron (Trieste, Italy) with a wavelength of 1.000 Å and a DECTRIS Pilatus 6M detector. Data were integrated and scaled using the program XDS . Data processing statistics are shown in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on crystals of the complexes were collected using synchrotron radiation at the XRD2 beamline at Elettra Synchrotron (Trieste, Italy) with a wavelength of 1.000 Å and a DECTRIS Pilatus 6M detector. Data were integrated and scaled using the program XDS . Data processing statistics are shown in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Data were integrated and scaled using the program XDS. 43 Data processing statistics are shown in the Supporting Information.…”
Section: Synthesis Of 4-(3-(4-(((2s3r4s5s6r)-345-trihydroxy-6-(hydrox...mentioning
confidence: 99%
“…Moreover, other studies identified further benzenesulfonamides possessing high hCA IX/hCA XII and improvement isoform selectivity. [11][12][13] Apart from the common zinc binding site (H94, H96, H119, T199), for the different hCAs the active site is well characterized by two distinct areas opposed each other controlling the enrolment of CO 2 and subsequent release of HCO 3 À . In more detail, the hCA IX is schematically composed of two halves: (i) the hydrophobic area is essentially lined by L91, V131, L135 and P202 residues; (ii) the hydrophilic area includes R60, R62, H64, Q67, T69, E170.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the compound named SLC‐0111 completed Phase II clinical trials for the treatment of hypoxic tumours and as adjuvant agent in advanced solid tumours. Moreover, other studies identified further benzenesulfonamides possessing high hCA IX/hCA XII and improvement isoform selectivity [11–13] …”
Section: Introductionmentioning
confidence: 99%
“…The structure of SLC-0111, a selective hCA IX inhibitor in phase I/II clinical trials for the treatment of advanced metastatic hypoxic solid tumors, was recently employed in our group for the preparation of a new class of 4-sulfamoyl­benzoyl­piperidine analogs with the aim of obtaining potent and selective hCA IX and XII molecules. With the intent to increase the knowledge about tail modification effects on the CA inhibitory activity and selectivity, in this study we present a small library of 1-(4-sulfamoyl­benzoyl)­piperidine-4-carbox­amide derivatives (Figure ). In these compounds, the benzene­sulfon­amide group is connected through a carbonyl group to a piperidine ring, facing the two tails with both the hydrophilic and hydrophobic regions of the active site.…”
mentioning
confidence: 99%